The Effect of Verification Experimental Methods on Science Process Skills and Chemistry Learning Achievement - Ni Wayan Diah Purnami Dewi M; I Wayan Subagia; I Wayan Redhana (Postgraduate, University of Mataram, 2023)
Learning by using the verification experimental methods could improve students' cognitive abilities and science process skills. However, there are inconsistent results when applying this method of science process skills and learning achievement. This study was conducted to describe and explain: the simultaneous differences in science process skills and learning achievement between students taught by verification experimental and conventional methods; the differences in student science process skills taught by verification experimental and conventional methods; and the differences in the students’ learning achievement taught by the verification experimental and conventional learning methods. This study was a quasi-experiment with a pretest-posttest design. The data analysis was conducted using descriptive analysis techniques and multivariate analysis (MANCOVA). The results of the study showed there are simultaneous differences in science process skills and students' learning achievement with an r square price of 0.743, or 74.3%; there are differences in the science process skills of students who studied using the verification experimental methods; and there are differences in students’ learning achievement; the experimental class was is higher than the control class. The other inconsistent results of the study on this method were caused by the different characteristics and cognitive levels of students